2014
DOI: 10.3899/jrheum.131137
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Clinical Remission in Patients with Systemic Lupus Erythematosus

Abstract: Prolonged remission is an infrequent outcome among patients and is preceded by an atypically monophasic clinical course in a significant minority. Those taking medications represent a heterogeneous group: those who will tolerate eventual taper, and those whose disease activity was merely suppressed by ongoing immunosuppression. Prolonged remission may reflect unique pathophysiologic mechanisms, and warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
99
2
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 31 publications
7
99
2
6
Order By: Relevance
“…In fact, remission in patients on treatment is more frequent than in those who are therapy-free. In a previous study by Steiman et al ,15 2.4% of patients (38/1613) achieved a clinical remission without taking corticosteroids and immunosuppressants, but this percentage doubled (4.5%, 72 patients) when considering remitted patients on medications.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In fact, remission in patients on treatment is more frequent than in those who are therapy-free. In a previous study by Steiman et al ,15 2.4% of patients (38/1613) achieved a clinical remission without taking corticosteroids and immunosuppressants, but this percentage doubled (4.5%, 72 patients) when considering remitted patients on medications.…”
Section: Discussionmentioning
confidence: 85%
“…Notably, other studies did not specify the dose of corticosteroids allowed in the definition of remission,7 15 18 thus including cases in which the disease was clinically quiescent, thanks to medium-to-high dose of steroids.…”
Section: Discussionmentioning
confidence: 99%
“…In adult patients, prolonged remission, defined as SLEDAI equal to zero for at least five years, was found in only 2.4%, confirming the low frequency of this status in a large cohort. 21 Other studies identified prolonged remission in only 2% to 7% of adult patients. 22 Despite difficult comparison in those studies due to differences in definitions of activity patterns and tools used, we observed a lower frequency of the LQ pattern, which in adults ranges from 4% to 44.3%.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, clinical remission has been defined by the absence of clinical features in the presence of immunological markers such as anti-dsDNA positivity and/or low complement serum levels [10]. There is no full agreement concerning the remission duration, the disease activity indices used to define remission, the serologic markers to be considered, and the allowed treatments [70]. Several authors agree that in clinical practice low-dose glucocorticoids (i.e.…”
Section: Definition Of Remissionmentioning
confidence: 99%